Neuroaxonal Dystrophy and Cavitating Leukoencephalopathy of Chihuahua Dogs. (September 2017) - Degl'Innocenti, Sara; Asiag, Nimrod; Zeira, Offer; Falzone, Cristian; Cantile, Carlo
A novel form of neuroaxonal dystrophy is described in 3 Chihuahua pups, 2 of which were from the same litter. It was characterized not only by accumulation of numerous and widely distributed axonal swellings (spheroids) but also by a severe cavitating leukoencephalopathy. The dogs presented with progressive neurological signs, including gait abnormalities and postural reaction deficits. Magnetic resonance images and gross examination at necropsy revealed dilation of lateral ventricles and cerebral atrophy, accompanied by cavitation of the subcortical white matter. Histopathologically, severe axonal degeneration with formation of large spheroids was found in the cerebral and cerebellar white matter, thalamus, and brainstem nuclei. Small-caliber spheroids were observed in the cerebral and cerebellar gray matter. The telencephalic white matter had severe myelin loss and cavitation with relative sparing of the U-fibers. Different from previously reported cases of canine neuroaxonal dystrophy, in these Chihuahuas the spheroid distribution predominantly involved the white matter with secondary severe leukoencephalopathy.